Astaxanthin protects against environmentally persistent free radical-induced oxidative stress in well-differentiated respiratory epithelium - Ayaho Yamamoto; Peter D. Sly; Lavrent Khachatryan; Nelufa Begum; Abrey J. Yeo; Paul D. Robinson; Stephania A. Cormier; Emmanuelle Fantino (Redox Biology)
Environmentally persistent free radicals (EPFRs) are combustion products present in substantial numbers on atmospheric particulate matter with half-lives of days to years. The mechanisms linking EPFR exposure and respiratory diseases are unclear, but likely involve oxidative stress. We investigated the mechanisms by which EPFR exposure impact on well-differentiated primary human nasal epithelial cells from subjects sensitive or resistant to oxidant stressors, cultured at an air-liquid interface. We found that EPFR exposure induced mitochondrial reactive oxygen species (mtROS) production; increased mitochondrial DNA copy number; down-regulated mucus production gene, Mucin-5AC (MUC5AC); up-regulated detoxifying gene, cytochrome P450 1A1 (CYP1A1), nuclear factor erythroid 2-related factor 2 (NRF2)-regulated antioxidant pathways including Sirtuin 1 (SIRT1)-Forkhead box O3 (FOXO3), mitophagy, PTEN-induced kinase 1 (PINK1), apoptosis, cyclin-dependent kinase inhibitor p21 (p21), and inflammation, C–C motif chemokine ligand 5 (CCL5). These results indicate that the well-differentiated respiratory epithelium can respond and activate redox reactions when exposed to sublethal concentrations of EPFRs. Increased susceptibility to EPFR exposure is conferred by failure to upregulate the mucin gene, MUC5AC, expression. Pre-treatment with astaxanthin prevented most of the negative impacts caused by EPFRs. Our results demonstrate that EPFRs can induce oxidative stress and cause damage to respiratory epithelium. A dietary antioxidant, astaxanthin, protected cells from EPFR-induced oxidant stress.